Estratégias de redução de risco percebido na compra e no consumo de carne bovina - Pereira, Luís Henrique (2005)
Confronted with alarming social discourse favouring the perception of food risk, modern consumers find themselves in a situation of psychological discomfort caused by consumption of foodstuffs coming from the agricultural and foodstuff industry. To eliminate this discomfort the consumer may change their purchasing and consumption habits or introduce some measures for the reduction of risk. Since Bauer first introduced the marketing world to the concept, perceived risk has had a long and varied research tradition, yet many authors have failed to recognize in their research how pervasive the construct is in all the stages of the buying process. Hundreds of studies have measured risk perception in wide variety of contexts but, in the vast majority of cases, the stage of decision process in which the consumer found himself/herself in at the time of measurement was not considered. Then, this research brings an innovation in this sense once it considers the whole decision make process in its analysis. Another important contribution of this work is to break with the traditional view of risk reduction models where the risk reduction is mainly linked to the search of information and done on the level of handled risk to consider that risk reduction may happen also with the help of practices and cognitive developments and can be done in two levels: inherent risk and handled risk. Hence, the aim of this work is to understand the way consumers perceive risk in the whole decision making process and to present a typology of risk reduction strategies taking into account the diversity of buying and consumption practices.